A level set based topology optimization for elastodynamic problems using BEM - Li, Huiwen; Gao, Haifeng; Liang, Jianguo; Li, Zhiqiang; Xu, Huidong; Zheng, Changjun (Frontiers in Physics, 2024)
The paper presents a topology optimization methodology for 2D elastodynamic problems using the boundary element method (BEM). The topological derivative is derived based on the variation method and the adjoint variable method. The level set method is employed for the representation of the material domain and voids within a specified design domain. Thus, the boundaries can easily be generated, following the zero isocontour of the level set function. Numerical implementation is carried out to demonstrate the effectiveness of the proposed topology optimization methodology in wave isolation and waveguide problems.